The integrated effect on properties and composition of high-paraffin oil sludge; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Anufriev R. V.; Volkova G. I.; Vasilyeva A. A.; Petukhova A. V.; Usheva N. V. Nataliya Viktorovna (2015, 2015)
Title screen